THE CALAMUS JAVENSIS (ARECACEAE: CALAMOIDEAE) COMPLEX IN HISTORICAL BIOGEOGRAPHIC CONTEXT - Mega Atria; Peter C van Welzen (BRIN Publishing (Penerbit BRIN), 2021)
ATRIA, M. & VAN WELZEN, P. C. 2021. The Calamus javensis (Arecaceae: Calamoideae) complex in historical biogeographic context. Reinwardtia 20(1): 1−7. — Calamus javensis is a very polymorphic species with a number of recognisable forms (of which several were once even recognized at species level). A historical biogeographic analysis showed no historical distribution pattern in the diversification of these various forms. The forms are very likely the result of adaptation to local circumstances, whereby more or less identical forms can develop under similar niche circumstances in disjunct areas, exceptions are the ‘acuminatus-polyphyllus’ form and C. tenompokensis that are recognisable and present in a non-disjunct area.